A Case Series Report of Unusual Presentations of Clinical Plasmodium Vivax Infection in District Bannu and Adjacent Areas (Medical Forum Monthly, 2024)
Objective: The objective of this study was a case series report of unusual presentations of clinical Plasmodium Vivax infection in district Bannu and adjacent areas.Study Design: Descriptive, case series.Place and Duration of Study: This study was conducted at the Department of Medicine, DHQ Teaching Hospital (DHDTH) Bannu, and Khyber Pakhtunkhwa. Study was carried out for a period of 12 months, from April 2016 to April 2017.Materials and Methods: Data were collected from 100 patients, who were having clinical vivax malaria but negative thick and thin smear, presented with unusual symptoms, signs and laboratory findings, from April 2016 to April 2017.Results: Out of 100 patients, 41 patients were males (41%) and 59 (59%) were females. All of these were having negative thick and thin smear for vivax malaria. Out of these, all 100 patients (100%) were having Headache and Splenomegaly (mild <4cm). 45 patients (45%) were having Arthralgia/ Myalgia (nonspecific, where no other obvious cause was found), 28 patients (28%) were having Lower Backache ( especially in young patients aged <35yrs, who were non-obese with BMI <23 Kg/M2), 44 patients (44%) having Calf Muscle Pain, 21 patients (21%) having Fever on alternate day (repeated after 48hrs), 17 patients (17%) having Mild jaundice (Bilirubin >1.1mg/dl but <4mg/dl, while G6PD was normal) , 50 patients (50%) having Pallor/Anemia (Hb<10mg/dl), 9 patients (9%) having Pain Abdomen (in school going aged <15yrs), 18 patients (18%) having Sense of bitter taste in mouth, 7 patients (7%) having no fever, 32 patients (32%) having Thrombocytopenia (platelets <150,000/microL) and 39 patients (39%) having Herpes labials.Conclusion: In our set up, Vivax malaria seems to be chronic and endemic, but undiagnosed on routine smear examination, and it has a diverse unusual clinical presentations. So it demands a high suspicion and vigilance on part of a physician for prompt diagnosis and early treatment, to decrease the disease burden and its complications